PEMUTAKHIRAN KURIKULUM DI PERGURUAN TINGGI - Anik Ghufron (Jurnal Cakrawala Pendidikan, 2007)
Lately there has been a strong trend at higher educationalinstitutions to update their curriculum. This phenomenon shows thatthe activity of curriculum development in such institutions is highlydynamic. It is quite reasonable because the curriculum is, after all,the very substance of schooling and the raison d 'etre for teachers atschools. The updating can be done totally or partially.Higher education curriculum updating is not a routine activitydone periodically. It is to be done when necessary and if possibleimmediately. And it needs to be perceived positively to improve thequality of instruction. Without it, instructional activity in highereducation becomes out of date.There are four steps in higher education curriculum updating: (1)reviewing the formulations of competencies, (2) reviewing thesubstance and format of the syllabus, (3) reviewing the model ofcurriculum implementation, and (4) reviewing the system ofevaluation